The vicious cycle of depressive symptoms and disability in older adults - Mengzhen Sun; Xiaoru Sun; Hui Zhang; Xiaoyan Jiang; Xiaofeng Wang; Qi Zhang (The Journal of Nutrition, Health and Aging)
Background: Unidirectional researches have suggested a correlation between depressive symptoms and disability, but it remains uncertain whether this association is bidirectional. Methods: The study is based on the 1st-10 th waves of the NHATS (National Health and Aging Trends Study). The subset A and subset B included 3,459 and 3,801 samples, respectively. A random-intercept cross-lagged panel model was employed to explore the bidirectional dynamic relationship between depressive symptoms and physical function indicators, including BADL (basic ADL), IADL (instrumental ADL), and ADL (a combination of BADL and IADL). Results: An increase in depressive symptoms led to a decline in physical function at all levels, and vice versa. When older adults experienced poorer physical function than usual, their subsequent depressive symptoms were stronger (BADL, β = 0.082, p < 0.0001; IADL, β = 0.072, p < 0.001; ADL, β = 0.098, p < 0.0001). Conversely, an increase in earlier depressive symptoms resulted in a future decline in physical function (BADL, β = 0.042−0.057, p < 0.05; IADL, β = 0.048, p < 0.05; ADL, β = 0.061, p < 0.01). Conclusions: This study is the first to reveal a mutually reinforcing spiral effect between increased depressive symptoms and declines in any level of physical function. These findings highlight the importance of prevention strategies guided by a unity of mental-physical approach, offering a new perspective for the coordinated management of mental and physical health, and providing scientific evidence for policymaking and resource allocation.